2017
DOI: 10.3329/bjp.v12i2.31950
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of DNCB-induced atopic dermatitis

Abstract: Atopic dermatitis is a skin disease characterized by allergic skin inflammation, redness and itching. The animal model is necessary to find out new drugs. The DNCB-induced animal model of atopic dermatitis includes the following steps: 1) Selection of animals; 2) Shaving of dorsal skin; 3) Applying DNCB once in 24 hours for three days; 4) Monitoring the development of atopy on day 4 post DNCB application. Further, the efficacy of reference drug can be determined by applying on the atopy skin, depends on the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…A mouse model similar to these diseases was used as a chronic inflammation model to validate in vitro results using TNFα or IFNγ treatment. So, we used DNCB solution ( 21 ) and IMQ cream ( 16 ) to establish these models and confirmed that the expression patterns of FRA1, c-JUN, HDAC1, and FLG in vivo were consistent with the in vitro data. These data suggest that normalizing the elevated expression levels of FRA1, c-JUN, or HDAC1 may be therapies for patients with AD or psoriasis.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A mouse model similar to these diseases was used as a chronic inflammation model to validate in vitro results using TNFα or IFNγ treatment. So, we used DNCB solution ( 21 ) and IMQ cream ( 16 ) to establish these models and confirmed that the expression patterns of FRA1, c-JUN, HDAC1, and FLG in vivo were consistent with the in vitro data. These data suggest that normalizing the elevated expression levels of FRA1, c-JUN, or HDAC1 may be therapies for patients with AD or psoriasis.…”
Section: Discussionsupporting
confidence: 61%
“…We found that the AP1 binding motif in the FLG promoter is crucial for FLG down-regulation and that TNFα + IFNγ treatment induces the formation of a repressor complex between FRA1:c-JUN components of AP1 and histone deacetylase (HDAC) 1. We confirmed the altered expression of FLG and the FRA1:c-JUN:HDAC1 complex in vivo using mouse models of DNCB-induced AD ( 21 ) and IMQ-induced psoriasis ( 15 ).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…A case-control study was done on 80 male Albino mice (20-30g) recruited from local markets, were treated with 1-Chloro-2,4-dinitrobenzene (DNCB)induced atopic dermatitis (Hamad et al, 2017) and compared with age and the sex-matched control group comprised of 20 healthy male Albino mice. The study was started in June and inished in December 2019.…”
Section: Methodsmentioning
confidence: 99%
“…When applied repeatedly to the skin, DNCB induces Th2-dominant immune response, causing elevation of serum IgE levels, overproduction of keratinocytes, and in ltration of mast cells. Among diverse substances that cause AD, DNCB is frequently used in AD research owing to it being affordable and its results being reproducible [9][10][11].…”
Section: Introductionmentioning
confidence: 99%